“Analytical Techniques for Development Planning” (A Review Of Tims' Multisector Model For Pakistan'S Third Plan (1965-70)) - Azizur Rahman Khan (Pakistan development review, 2022)
In the present decade there has been a great proliferation of multisectoral models for planning. Part of the incentive has certainly been the potentiality of their application in formulating the actual plans. By now there have been so many different types of multisectoral models that it is useful to attempt some kind of classification according as whether or not they embody certain well-known features. The advantage of such a classification is that one gets a general idea about the structure of the model simply by knowing where it belongs in the list of classification. One broad principle of classification is based on whether the model simply provides a consistent plan or whether it also satisfies some criteria of optimality. A multisectoral consistency model provides an allocation of the scarce resources (e.g., investment and foreign exchange) in such a way that the sectoral output levels are consistent with some given consumption or income target, consistency in this context meaning that the supply of each sector's output is matched by demand generated by intersectoral and final use at base-year relative prices. To the extent that the targets are flexible, there may be many such feasible plans. An optimizing model finds the "best" possible allocation of resources among sectors, the "best" being understood in the sense of maximiz¬ing > a given preference function subject to the constraints that ensure that the plan is also feasible.